Etyczne aspekty wykonywania działalności akwizycyjnej na rzecz otwartych funduszy emerytalnych - Nerka, Arleta (Annales. Etyka w Życiu Gospodarczym, 2011)
Canvassing has become a profession following the pension system reform that established open pension funds collecting contributions from individuals. Because pension insurance performs social functions, it is necessary to ensure that the canvassers demonstrate professionalism as well as the necessary ethical attitudes. This means that the appropriate legal criteria for their selection must exist and that the persons themselves should meet integrity and moral requirements, so that the reliability of services is guaranteed. Canvassing focuses on persuading individuals to join an open pension fund (OPF) or remain its member so it plays a relatively important role. In the first place, the canvassers impart knowledge on how the pension system works, on the importance of being an OPF member, etc. Besides, canvassing accounts for a large part of OPFs’ financial management that spent increasingly large amounts to acquire new members as reported by the Polish Financial Supervision Authority. Poaching members of other OPFs, particularly those with long membership, is an effective way for a fund to increase the value of its assets, however multiplying the canvassing costs. The insured themselves are also affected, as the canvassers compete for them ruthlessly, reaching sometimes for ethically dubious methods.